Government Expending, Real Interest Rate, and Economic Growth in Nepal - Chaudhary, Arbind; Acharya, Mahesh (Economic Journal of Nepal, 2018)
This paper aims to obtain a linear and causal relationship between government expenditure and real interest rate to the economic growth of Nepal for 1975-2015. The applied ARDL cointegration technique yields a long-run association among the variables. Furthermore, the variables: government expenditure, real interest rate, and other control variables-average rainfall and trade openness are established as long-run elements to the national income. The real interest rate has a substitution effect on the Nepalese household sector, hence it hurts the real income. However, trade openness, public expenditure, and average rainfall are recorded as the short-run determinants. Similarly, the study also explores the existence of a bidirectional causal relationship between government expenditure and real income.